Ocena vpliva vhodnih parametrov v analizi toplotnega prehodnega pojava pod tlakom v reaktorski posodi Nuklearne elektrarne Krško v primeru majhne izlivne nezgode - Bašič, Ivica (Strojniški vestnik, 2006)
This paper focuses on the deterministic method of limiting cases of the Krsko Nuclear Power Plant (NPP) reactor pressure-vessel cooling by mediating the emergency core-cooling system (ECCS) during a small-break loss-of-coolant accident (SB LOCA). The SB LOCA accident with the equivalent diameter break of50.8 mm in the cold leg and the RELAP5/MOD3.3 computer code were selected for the basic calculation. In further study, by modifying the ECCS's parameters for the same break, three accidents of the SB LOCA were simulated. The purpose of our study was to estimate the potential risk of the extreme conservative input parameters for the pressurized thermal shock (PTS) in the reactor's pressure vessel.
Keywords: reaktorji jedrski; posode reaktorske; pojavi prehodni; nezgode izlivne male; Nuklearna elektrarna Krško; jedrski reaktorji; izlivne nezgode; modeli; simulacije